Effect of predator exclusion on cassava infested with tetranychid mites (Acari: Tetranychidae) - Braun, Ann R.; Bellotti, Anthony C.; Guerrero, J.M.; Wilson, LT (1989)
Chemical exclusion of predators with permethrin was used to test the effectiveness of the phytoseiid predator Amblyseius limonicus Garman and McGregor and a complex of minor predators in the biological control of tetranychid (Mononychellus spp., Tetranychus spp., and Oligonychus peruvianus McGregor) pests of cassava, Manihot esculenta Crantz. Mononychellus spp. and Tetranychus spp. populations were significantly higher and predator populations significantly lower in permethrin-treated plots than in control plots. Numbers of O. peruvianus were not affected by permethrin. Yield of fresh commercial roots and of dry matter was significantly higher in plots with predators than in plots where permethrin was applied every 2 wk for predator exclusion. Yields of neither fresh nor dry matter in control plots were significantly different from yields in plots that had been protected with acaricide, suggesting that predation kept spider mite populations below economically damaging levels. Publication date: 01 August 1989